The Influence of COVID-19 on Sustainable Economy - Vukovic, Darko; Maiti, Moinak; Frömmel, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book examines applied studies contributing to the issues of financial markets and sustainable economy in conditions of COVID-19 pandemic. All studies in this book applied complex models with quantitative data in the areas of finance, macro and sustainable economy, as well as business and management, to express the main issues of the financial-economic universe during the pandemic crisis. Some of the studies offer possible solutions in the sustainable post-COVID era. This book is also of particular interest in relation to the green economy during the COVID-19 pandemic.